(untitled) - Sheldon, Walt (New York, 1965)
This is the story of the extraordinary period from the end of the war in 1945 to the signing of the Dulles Treaty in 1952, when four million Americans took part in the occupation of Japan.
Keywords: Japan; History; Allied occupation, 1945-1952